Green synthesized Moringa oleifera Leaf Powder – Silver Nanoparticles (MOLP-AgNPs) promotes apoptosis by targeting Caspase-3 and Phosphorylated-AKT signaling in MCF-7 cells - Happy Kurnia Permatasari; Sa'diyatul Rizqie Amaliyah Firdaus; Hendra Susanto; Nik Ahmad Nizam Nik Malek; Widodo; Holipah; Hikmawan Wahyu Sulistomo (Journal of Agriculture and Food Research)
High mortality rates of breast cancer have been known as a significant health problem among women. As a widely consumed plant, Moringa oleifera contains many phytochemical constituents that can inhibit cancer cell activity. This study involves using Moringa oleifera to impede the development of cancer cells through green-based silver nanoparticle synthesis by targeting programmed cell death. Different analytical techniques were used to analyze the synthesized AgNPs, and it showed that MOLP-AgNPs have a spheroid form, and its surface plasmon resonance (SPR) was detected in the 476–478 nm range. Based on the total viable cells through dye exclusion assay, it showed that MOLP-AgNPs significantly reduced breast cancer cell viability, and there was no significant cytotoxic activity of MOLP-AgNPs against non-cancerous cells after 24 h investigation. Caspase-3 is an apoptosis-related protein and phosphorylated AKT, which plays a crucial role in cell growth and may interact with AgNPs indirectly. It was observed that MOLP-AgNPs promote apoptosis through Caspase-3-dependent signaling and inhibit AKT phosphorylation in a dose-dependent manner. These findings indicated that MOLP-AgNPs have the potential for further development as anticancer drugs, particularly for breast cancer.